Evaluation of the Deadly Liver Mob program: insights for roll-out and scale-up of a pilot program to engage Aboriginal Australians in hepatitis C and sexual health education, screening, and care - Carla Treloar; Max Hopwood; Elena Cama; Veronica Saunders; L. Clair Jackson; Melinda Walker; Catriona Ooi; Ashley Ubrihien; James Ward (BMC, 2018)
Abstract Background Deadly Liver Mob (DLM) is a peer-driven, incentivised health promotion program aimed at increasing understanding of hepatitis C, promoting harm reduction in relation to injecting drug use, and linking participants to screening for hepatitis C, other blood borne viruses and sexually transmissible infections among Aboriginal people in Western Sydney, NSW. This paper presents the evaluation of a pilot study examining the acceptability of the program as a first step of a scalability assessment. Methods Deadly Liver Mob operated in co-located needle and syringe programs and sexual health clinics in two sites: (Site 1: two and a half years for 2 days/week; Site 2: 1 year for 1 day per week). Comparisons were made of the proportion of Aboriginal clients (Site 1) and occasions of service provided to Aboriginal clients (Site 2) in the 12 months prior and post-introduction of DLM. Interviews were conducted with 13 staff involved in delivery of DLM and with 19 clients. Results A total of 655 and 55 Aboriginal clients, respectively, attended Site 1 and Site 2 for health education. The proportion of Aboriginal clients attending both sites was significantly higher during the DLM compared with prior to its implementation. Of those attending for health education, 79 and 73%, respectively, attended screening following education. DLM clients strongly endorsed the program. Some staff were concerned about workforce capacity to effectively engage Aboriginal clients with multiple and complex needs, managing the differing aims of the participating services involved, and about offering of incentives for attendance at health services. Conclusion While acceptability was high among staff and clients and preliminary results show high engagement with Aboriginal communities, this evaluation of a pilot program raises some issues to consider in scale up of DLM to other sites. The initiation of additional DLM sites should address issues of alignment with governing strategies and workforce capacity.